Do accounting and finance tools serve governance? - Syed Mohamed, Mohamed Ariff; Ratnatunga, Janek (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
A brief review of recent literature on corporate governance is provided, which is then concluded with a proposed corporate governance framework as a starting point for further development. We propose that it is stakeholder concentration that determines the quality of corporate governance. Next objective of this paper is the more ambitious one of addressing the role of accounting and finance disciplines to serve corporate governance. We test empirically if the use of some accounting and finance tools would have alerted management, auditors and regulators as well as investors to the impending collapse of failed firms ahead of time. If performance deterioration is not verifiable by using such acclaimed tools of these disciplines, then the advocacy of these disciplines is untenable and their contribution is overstated. Careful application of accounting-cum-finance tools, it appears, would have pre-identified the financial weakening of troubled firms, well ahead of time to catastrophic failures.